Enhancing volunteerism in healthcare: mediating effect of social network - Alias, Siti Noormi; Ismail, Maimunah; Suandi, Turiman; Omar, Zoharah (Human Resource Management Academic Research Society, 2018)
The participation of volunteers in volunteerism activities particularly in combating healthcare issues among underserved communities is highly demanded. Volunteerism refers to intangible contributions of time and effort spent to help those people in straitened circumstances in a community. Volunteerism is a type of philanthropic behavior. This study explored how social network acts as a mediator in the relationships between coping strategies and social trust with volunteerism. This study used a correlational research design involving 300 community health workers (CHWs) under MERCY Malaysia, a non-government organization (NGO) in the healthcare sector. Data were analysed using a two-step approach in structural equation modeling (SEM). Results showed that social network mediated the relationship between task-oriented coping and volunteerism in community healthcare. This study gives insights to managers and NGOs in hiring and retaining CHWs in community development work based on a developing country context.